PERANCANGAN STRATEGI PEMASARAN PRODUK MAKANAN PADA UMKM HEAVEN CRUMBS - Rana Salsabila Deani (2021)
Heaven Crumbs is one of the businesses engaged in the culinary field. Heaven Crumbs comes with a product in the midst of a market that has been formed with already fierce competition. The problem with this business is that Heaven Crumbs only reaches its highest sales points at certain times such as Christmas and Eid. Outside of this time, sales tend to be lower due to less customer interest. Therefore, research was conducted to design the right marketing strategy to be implemented in Heaven Crumbs based on internal and external factors, Internal-External matrix, SPACE Matrix, SWOT, and AHP. The first stage is the input stage, which is doing identification to get the attributes of internal factors and attributes of external factors. The second stage is the matching stage which consists of the Internal-External Matrix, SPACE Matrix, and SWOT. This stage matches the type of strategy generated based on the previous stage. The results of the matching stage are strategies that are market penetration, market development, and product development. From these results, decisions are made using AHP at the decision stage, so that the main factors that play the biggest role in marketing strategy are digital marketing, the main actor who plays a role is the production department, and the chosen alternative strategy is optimization digital marketing.